How does cooperation affect innovation in micro-enterprises?. Issue 8 (20th August 2014) - Tu, Chiayu; Hwang, Shiuh-Nan; Wong, Jehn-Yih
Abstract : Purpose: This research investigates how micro-enterprises cooperate with external parties in order to promote innovation and entrepreneurial success. The paper describes supplier and consumer cooperation and analyzes how these two behavioral modes influence the product and service innovations of micro-enterprises. Based on the resource-based view of the firm, we show that micro-enterprises help the source of innovation by tapping into the resources and abilities of suppliers. Design/methodology/approach: This research used a questionnaire to randomly sample micro-entrepreneurs that run stalls at night markets. Before distributing the final questionnaire, we in depth interviewed 10 micro-entrepreneurs and asked them to openly describe their entrepreneurial processes and success stories. Findings: The results of this study show that cooperation with consumers does not improve product and service innovations. By contrast, the cooperation of micro-enterprises with suppliers was found to increase the generation of product and service innovations in the present study. And the findings show that the effect of innovation approaches on entrepreneurial success indicates that product innovation positively improves firm performance. Last, from the perspective of cooperation behavior, product innovation mediates entrepreneurial success through cooperation with suppliers. Research limitations/implications: Because of respondents were night market vendors and thus the results are not necessarily generalizable to other types of micro-enterprises. Therefore, researchers are encouraged to test multiple types of micro-enterprises. Second, this research aimed to differentiate the relationships between innovation approaches and entrepreneurial success by focusing exclusively on product and service innovations. Therefore, other variables should be included in future studies. Practical implications: As for practical implications in the field of cooperation behavior, we have shown that it is crucial to maintain long-term cooperative relations with trusted suppliers. Originality/value: This paper fulfills an identified need to study how innovation in micro-enterprises.